Analisis Yuridis Asas Fiksi Hukum dari Prespektif Hukum Pidana Dalam Kasus Illegal Logging di Probolingo - Ida Bagus Wisnuputra Raditya; I Dewa Gede Dana Sugama (Pusat Riset dan Inovasi Nasional, 2024)
The principle of Ignorantia Jurist is a principle that assumes everyone knows the law since the law is legal. Although its implementation is needed to achieve the purpose of the regulation, there is no barrier to its application. In the case of illegal logging in Probolingo with the verdict number 179/PID.B/2014/PN. PBL, the defendant has a background that makes it very possible for him not to know the regulation in the indictment. The purpose of this research is to find out how the application of the principle from the point of view of criminal law relates to the verdict number 179/PID.B/2014/PN. PBL. This research was written using the normative writing method to analyze the ambiguity of the norms governing the principles of Ignorantia Jurist.